Multisensory temporal binding window in autism spectrum disorders and schizophrenia spectrum disorders: A systematic review and meta-analysis. (March 2018) - Zhou, Han-yu; Cai, Xin-lu; Weigl, Michael; Bang, Peter; Cheung, Eric F.C.; Chan, Raymond C.K.
Highlights: Multisensory temporal dysfunction represented by an extended temporal binding window is a common feature of ASD and SSD. Unisensory temporal acuity is impaired in schizophrenia but may be spared in ASD. Multisensory dysfunction is associated with incoherent perception and communicative deficit that characterize SSD and ASD. Abstract: Multisensory temporal integration could be compromised in both autism spectrum disorders (ASD) and schizophrenia spectrum disorders (SSD) and may play an important role in perceptual and cognitive impairment in these two disorders. This review aimed to quantitatively compare the sensory temporal acuity between healthy controls and the two clinical groups (ASD and SSD). Impairment of sensory temporal integration was robust and comparable in both patients with SSD (Hedges' g = 0.91, 95%CI[0.62–1.19]; Z = 6.21, p  < .001) and ASD (Hedges' g = 0.85, (95%CI[0.54–1.15]; Z = 5.39, p  < .001). By further separating studies into unisensory and multisensory (bimodal: audiovisual) ones, subgroup analysis indicated heterogeneous and unstable effects for unisensory temporal binding in the ASD group, but a more consistent and severe impairment in multisensory temporal integration represented by an enlarged temporal binding window in both clinical groups. Such multisensory dysfunction is associated with symptoms like hallucinations and impaired social communications. Future studies focusing on improving multisensory temporal functions may have important implications for the amelioration of schizophrenia and autistic symptoms.